Cell culture systems: invaluable tools to investigate lignin formation and cell wall properties. (April 2019) - Pesquet, Edouard; Wagner, Armin; Grabber, John H
Graphical abstract: Abstract : Although the use of cell culture systems in Plant Biology and Biotechnology has been limited compared to other areas of Life Sciences, plant cell cultures capable of lignifying on demand have proven invaluable in unravelling the lignification process and its impact on biomass utilization. Inducible cell cultures have enabled researchers to decipher multiple levels of cellular control used in and between plant cells to define the spatiotemporal deposition, composition, structure, and quantity of lignin. Artificially lignified cell cultures have also been used to determine the effects of lignin composition on the susceptibility of cell walls to chemical treatments, and digestion by rumen microflora or fungal enzymes. Plant cell cultures have enabled the fast-tracking of lignin-related research and provided insights into the lignification processes that could not have been easily obtained by using whole plants as model systems.